1995
DOI: 10.1038/ng0495-401
|View full text |Cite
|
Sign up to set email alerts
|

In vivo amplification of the androgen receptor gene and progression of human prostate cancer

Abstract: Overexpression of amplified genes is often associated with the acquisition of resistance to cancer therapeutic agents in vitro. We have identified a similar molecular mechanism in vivo for endocrine treatment failure in human prostate cancer which involves amplification of the androgen receptor (AR) gene. Comparative genomic hybridization shows that amplification of the Xq11-q13 region (the location), is common in tumours recurring during androgen deprivation therapy. We found high-level AR amplification in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
879
1
5

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 1,311 publications
(921 citation statements)
references
References 16 publications
36
879
1
5
Order By: Relevance
“…Androgen receptor gene amplifications are uncommon in hormone-sensitive tumours and are present in 20 -30% of hormoneresistant tumours (Visakorpi et al, 1995;Koivisto et al, 1997;Bubendorf et al, 1999;Miyoshi et al, 2000;Edwards et al, 2001). In the present study, we investigated AR amplification, AR protein expression and PSA expression in paired hormone-sensitive and hormone-resistant tumours from the same patient with documented initial responses to androgen deprivation therapy.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Androgen receptor gene amplifications are uncommon in hormone-sensitive tumours and are present in 20 -30% of hormoneresistant tumours (Visakorpi et al, 1995;Koivisto et al, 1997;Bubendorf et al, 1999;Miyoshi et al, 2000;Edwards et al, 2001). In the present study, we investigated AR amplification, AR protein expression and PSA expression in paired hormone-sensitive and hormone-resistant tumours from the same patient with documented initial responses to androgen deprivation therapy.…”
Section: Discussionmentioning
confidence: 88%
“…In the light of this observation it is possible, though at present unproven and to our view unlikely, that AR amplification does not mediate hormone resistance. It is hypothesised that AR gene amplification is involved in the development of hormone-resistant prostate cancer due to amplification, resulting in an increase in AR protein expression (Visakorpi et al, 1995). Real-time RT -PCR demonstrated that even one additional copy of the AR gene may increase AR expression (Linja et al, 2001), suggesting that even a small increase in relative gene dosage could have biological significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Amplification of the AR gene was seen in approximately 20-30% of all HR tumors. [18][19][20][21][22][23] In addition, there was heterogeneity in the amplification seen within tumors. 22 These studies indicated that since amplification is seen in refractory tumors, only the clones having the amplifications would be selected for further growth in a low-androgen environment, and would accumulate the chromosomal changes with time to establish aggressive disease.…”
Section: Amplification Of the Armentioning
confidence: 99%
“…The preclinical basis for this is manifold: (1) a frequent change following the development of metastatic castration resistant disease is the mutation, gene amplification and/or overexpression androgen receptor (AR) [9]; (2) several studies utilising diverse methodologies suggest that it is the intracrine and paracrine effects of in situ androgen synthesis or circulating adrenal derived steroid precursors that significantly contribute to prostate cancer growth [10] and (3) there appear to be multiple abnormalities within the AR pathway, involving coactivators and corepressors (~100% in CRPC metastatic samples) that predispose to AR pathway activation [11]. To date, there are broadly two new classes of hormonally active drugs in development: more effective AR antagonists (such as MDV3100, ARN-509, TOK-001) and inhibitors of the androgen biosynthetic pathway [such as abiraterone, TAK-700 (orteronel)].…”
Section: Introductionmentioning
confidence: 99%